2017
DOI: 10.1101/203851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Mining, Characterization and Development of miRNA-SSRs inArabidopsis thaliana

Abstract: 9Simple Sequence Repeats (SSRs), also known as microsatellites are short tandem repeats of that their occurrence within microRNAs (miRNA) genes has received attention. As is widely were mined. The sequences were retrieved by annotations available at EnsemblPlants using 3 1BatchPrimer3 server with miRNA-SSR flanking primers found to be well distributed. Our confirm that miRNA-SSRs were commonly spread across the full length pre-miRNAs, we 3 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Genic SSR markers designed from heat-stress-associated genes were screened over heat-tolerant and heat-susceptible wheat genotypes to study the genetic diversity and association between SSR markers and traits of heat stress tolerance ( Sharma et al, 2020 ; Manjunatha et al, 2021 ). Previous reports confirmed the presence of SSRs in pre-miRNA sequences of many plant species including Arabidopsis , rice, wheat, and Brassica in response to different abiotic stresses ( Ganie and Mondal, 2015 ; Kumar A. et al, 2017 ; Singh et al, 2017 ; Tabkhkar et al, 2020 ). There are very few reports for genetic diversity studies in heat-tolerant and heat-responsive wheat genotypes that used miRNA-SSR as molecular markers.…”
Section: Introductionsupporting
confidence: 57%
“…Genic SSR markers designed from heat-stress-associated genes were screened over heat-tolerant and heat-susceptible wheat genotypes to study the genetic diversity and association between SSR markers and traits of heat stress tolerance ( Sharma et al, 2020 ; Manjunatha et al, 2021 ). Previous reports confirmed the presence of SSRs in pre-miRNA sequences of many plant species including Arabidopsis , rice, wheat, and Brassica in response to different abiotic stresses ( Ganie and Mondal, 2015 ; Kumar A. et al, 2017 ; Singh et al, 2017 ; Tabkhkar et al, 2020 ). There are very few reports for genetic diversity studies in heat-tolerant and heat-responsive wheat genotypes that used miRNA-SSR as molecular markers.…”
Section: Introductionsupporting
confidence: 57%
“…The study suggested that a complex biological process mediated by miRNA-mRNA networks controls the seed type in pomegranate. The presence of genetic variations in pre-miRNAs and miRNAs are known to affect quantitative trait expression ( Ferrao et al, 2015 ), hence DNA markers may be developed from the miRNA regions to assist the procedure of trait improvement ( Kumar et al, 2017 ). Study by Joy et al (2018) showed presence of SSRs in pre-miRNAs and the authors proposed a role for alternative splicing in creating mature RNA isoforms in response to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Plants experience several environmental stresses that adversely affect their growth and development [71,72]. Abiotic stresses such as cold, drought, heat, light, oxidation, and salt are the major ones that limit the growth and productivity of crop plants to a large extent [73,74].…”
Section: Discussionmentioning
confidence: 99%